The future prospects for SiPM based receivers for visible light communications - Zhang, L; Chun, H; Ahmed, Z; Faulkner, G; O'Brien, D; Collins, S (IEEE, 2019)
A silicon photomultiplier (SiPM) could be used to create visible light communications receivers whose sensitivity is determined by shot-noise. However, its finite output pulse width will limit its bandwidth and its recovery time and dark count rate could limit its sensitivity. In this paper, a method of accurately determining the signal levels needed to transmit data in a shot-noise limited system using PAM is described. In addition, a method of estimating the additional power needed to use equalisation to overcome inter-symbol interference caused by the finite output pulse width of SiPMs is described. The best way to achieve more than 1 Gbps with this type of receiver and how to select the best available SiPM as a receiver are then discussed.